A study on determinants of workplace accidents through Occupational Safety and Health (OSHA) management in Staffield Country Resort Berhad / Nurfarah Ellina Hazman - Hazman, Nurfarah Ellina (Faculty of Business & Management, 2017)
Accidents in the workplace is a something that cannot be predict where and when it will happen but it is a preventable event before it is too late. As an employees in the organization, they need to stay alert and aware at all time to avoid accidents while manager need to investigate what are the causes that might influence workplace accidents and try to find a solutions about the problem. Existing recorded indicated that the present Organization Safety and Health (OSHA) in the workplace is still low and below expectation. Thus, this research addresses the determinants of workplace accidents through Ocupational Safety and Health (OSHA) Management in Staffield Country Resort Berhad. This study is conducted to determine the relationship between individual factors as measured by (stress and fatigue and unsafe act) also nature of job as measured by (machineries and tools, design of workplace and training procedure) with workplace accident. The study that has been conducted was using quantitative study while the research instrument that being used is self-administered questionnaire. Besides that, cluster sampling has been used as the sampling method and the total number of respondent is 76 person. In addition, this study has been used Statistical Package for the Social Science (SPSS) Version 20 to analyze the data analysis and findings. Therefore, it is found that stress and fatigue, unsafe act and design of workplace significantly influence workplace accident.